Edukasi Pemasaran Kreatif Bagi UMKM Kaos Bengkulu Berdasarkan Praktik Usaha Omah Oblong Yogyakarta - Avrilina Nur Fadhillah; Tera Andini Wulansari; Vanisa Ramadhani; Monda Monda; Veny Puspita (Rengganis Jurnal Pengabdian Masyarakat, 2026)
The low adoption of modern marketing strategies and the lack of cultural-based product differentiation are the main constraints facing the development of garment and souvenir t-shirt MSMEs in Bengkulu City. This community service activity aimed to educate and improve the capacity of t-shirt MSMEs in Bengkulu by implementing creative marketing strategies and storytelling. The target partner was the "Bengkulu T-Shirt Craftsmen Association," involving 25 active micro-business participants in collaboration with the Faculty of Economics and Business, UNIHAZ. The implementation method consisted of three main phases: preparation, execution (intensive training, industry visits to Omah Oblong Yogyakarta, and workshops), and evaluation using pre-test and post-test instruments. Quantitative evaluation showed a significant increase in participants' understanding, with the average comprehension score rising from 42% to 88%. Qualitatively, participants successfully formulated a content marketing blueprint based on Bengkulu's cultural potential, such as the Besurek fabric motif and local historical icons. The output proves that adapting a culture-based educational business model is highly effective in improving creative market orientation for local MSMEs.